THE HIGHLIGHT OF USING ONE-MINUTE TALK TECHNIQUE TO IMPROVE STUDENTS’ SPEAKING SKILL - Apriliya, Khairina; Nursidah, Nursidah; Ilyas, Ilyas (International Journal of Research on English Teaching and Applied Linguistics, 2024)
This research aimed to find out whether or not the use of one-minute talk technique improves students' speaking skills in the English education program at Universitas Muhammadiyah (UNIM) Bone. The research's population consisted of 40 second-semester students from the English education program at UNIM Bone in the academic year 2023-2024. The sample number was 20 students, chosen through purposive sampling. A quantitative approach was used in this research by using the model of classroom action research design developed by Kemmis and McTaggart. The instruments of this research were speaking test and speaking rubric. It focused on students’ speaking skills in terms of pronunciation, vocabulary, grammar, and fluency. The result of this research showed that the students’ improvement from the pre-test to the second cycle was highly improved, where the students’ success in the speaking skill test in the pre-test was 59.5, then in the first cycle was 71.9, and in the second cycle was 82.9. So it can be concluded that one-minute talk technique in the teaching and learning process can improve students' speaking skills in terms of pronunciation, vocabulary, grammar, and fluency in the second semester of the English education program at UNIM Bone.